Optimization of the Composition and Properties of Effective, Wide Format, Ceramic Stones - Fakhritdinovich, Bakhriev Nuritdin; Yoqubboyevich, Nurmatov Gofirjon (European Journal of Life Safety and Stability (2660-9630), 2022)
Energy saving is currently considered by developed countries as the most important national environmental and economic problem. Measures that ensure energy conservation are more cost-effective than those from the creation of energy resources. The rational use of fuel, raw materials and other material resources is becoming a decisive factor in the successful development of ceramic production in the context of economic reforms and unfavorable environmental conditions in the developed countries of the world. In this regard, the problem of obtaining large-format ceramics in the production of wall materials is a particularly urgent and unresolved problem. This article presents the results of scientific research and laboratory testing of the introduction of screenings from the Angren coal basin in the production of porous large-format wall stones. Attempts have been made to modify the composition of the molding sand used for the production of wall stones. As a result, high rates of heat-insulating, multi-slit wall stones were obtained, which is one of the promising areas in the field of energy-efficient construction.